In silico analysis to elect superior bacterial alkaline protease for detergent and leather industries - Das, Kamonashis; Chakraborty, Sourav; Hasan, Mahmudul; Shovo, Abdullah Maruf Rahman (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2016)
Alkaline protease contributes 40% of the total worldwide enzyme sales. Alkaline protease that is stable at very high temperature and pH is massively desirable for detergent industry and leather industry specially in tanning process. So the present study aims to elect superior bacterial alkaline protease (high temperature and pH stable) as compared to the alkaline proteases of currently industrially used bacteria (Bacillus subtilis and Bacillus cereus). A total of 50 protein sequences of alkaline proteases of different bacteria were analyzed through in silico characterization. ProtParam result revealed that isoelectric point and aliphatic index of alkaline protease of Bacillus megaterium were 8.83 and 93.35 respectively. In case of alkaline protease of B. megaterium, these two properties were significant in comparison to alkaline proteases of industrially used bacteria and other considered bacteria. A common motif of 28 amino acid residues i.e., IQSTYPGEDYEYMSGTSMATPHVAGVAA was found using MEME software in 46 protein sequences. It can be concluded that alkaline protease of Bacillus megaterium may be superior to alkaline proteases of industrially used bacteria and other considered bacteria. In addition, obtained common motif indicates its probable role in catalytic function and structure of alkaline proteases.